2021
DOI: 10.1186/s12913-021-06754-0
|View full text |Cite
|
Sign up to set email alerts
|

Health insurance enrollment and vision health in rural China: an epidemiological survey

Abstract: Background Vision health is an important aspect of health worldwide. Visual impairment (VI) is associated with poor quality of life and is usually more prevalent in rural areas. To help rural populations obtain vision care, health insurance policies have emerged throughout the world. However, some existing literatures show that health insurance enrollment’s impact on the overall physical health of rural population has been minimal. Focusing on vision health among adults in rural China, our stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…The above reasons may prompt this association to be stronger in women. Our result also showed that individuals with lower education levels are more likely to have VI, which may be that they are less likely to have health insurance or healthcare and worse health conditions [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 73%
“…The above reasons may prompt this association to be stronger in women. Our result also showed that individuals with lower education levels are more likely to have VI, which may be that they are less likely to have health insurance or healthcare and worse health conditions [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 73%
“…We observed urban-rural differences in the trends of vision impairment, although the discrepancy in the prevalence diminished after adjusting for all covariates. A plausible explanation is that rural older people in China bear higher financial burdens than urban residents when seeking eye care services before the New Cooperative Medical Scheme was established in 2003 [42]. Moreover, the shortage of eye care professionals in rural areas could limit access to ophthalmic services, therefore contributing to the high vision impairment prevalence among rural older adults [42].…”
Section: Discussionmentioning
confidence: 99%
“…A plausible explanation is that rural older people in China bear higher financial burdens than urban residents when seeking eye care services before the New Cooperative Medical Scheme was established in 2003 [42]. Moreover, the shortage of eye care professionals in rural areas could limit access to ophthalmic services, therefore contributing to the high vision impairment prevalence among rural older adults [42]. Although the number of ophthalmologists and county-level hospitals has increased since 2003, exceeding the goal of Vision 2020, these resources are distributed unequally across China, as most are allocated to urban areas [27,43,44].…”
Section: Discussionmentioning
confidence: 99%